The Effect of Work Motivation and Soft Skill Training on Employee Performance through Competence - Syah, E. Anisa Safa’at Derajat; Sanusi, Fauji; Imron, Ali (Economics and Business Journal (ECBIS), 2026)
This study examines the effect of work motivation and soft skill training on employee performance with competence as a mediating variable. The research was conducted at the Office of Women’s Empowerment, Child Protection, Population Control, and Family Planning (DP3AKB) of Banten Province. A quantitative approach with a census method was applied, involving all 134 employees as respondents. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that work motivation and soft skill training have positive and significant effects on employee performance. Furthermore, both variables significantly influence employee competence. Competence also has a positive and significant effect on employee performance and partially mediates the relationship between work motivation and performance as well as between soft skill training and performance. These findings suggest that improving employee performance in public sector organizations requires integrated human resource development strategies focusing on motivation enhancement, effective soft skill training, and systematic competency development.